Jack Unterweger - an authorship analysis of the notorious killer's autobiography "Fegefeuer oder die Reise ins Zuchthaus" - Marko, Karoline; Locker, Alesia (Language and Law / Linguagem e Direito, 2024)
Jack Unterweger, a notorious killer and celebrated author, was a highly skilled manipulator and was caught more than once to have plagiarized poems and short stories (Herwig, 2022; Leake, 2010). Praised for his work as an author, and particularly for his autobiography “Fegefeuer oder die Reise ins Zuchthaus”, Unterweger was released from prison in 1990. Almost 40 years after the publication of his autobiography, rumors have been voiced that Unterweger might not have written his autobiography by himself and that Sonja von Eisenstein, one of Unterweger’s benefactors and supporters, might have been involved in the writing of it (Herwig, 2022). Thus, based on a corpus of nine books by Unterweger and von Eisenstein, this study sets out to investigate whether these rumors are potentially true. The analysis is carried out with the help of a combination of quantitative (HCA, PCA) and qualitative (stylistic) methods. The analysis shows that Unterweger’s writing style is similar to the one of the questioned autobiography, but that someone else’s writing style is also present.